Widths of sets of functions of discrete variable - Velikin, V. L.; Velikina, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We obtain exact values of Kolmogorov and linear widths of arbitrary dimension for sets of functions of discrete variable with bounded difference of a given order.